Technology-Based Arabic Language Learning Model that Combines Digital Traditions and Innovation in Islamic Education - Rahmaini Rahmaini; Muhammad Shaleh Assingkily (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This research aims to design and develop a technology-based Arabic language learning model that combines Islamic scientific traditions with digital innovations, and to test the model's initial implementation in the context of Islamic education. The research uses a Design-Based Research (DBR) approach, which includes four stages: needs analysis, model design, initial development and implementation, and evaluation and revision. Data were collected through observations, interviews, documentation, and questionnaires with teachers and students in madrasas, then analyzed using simple qualitative and quantitative descriptive methods. The results of the study show that the learning model developed can increase student engagement in learning, facilitate the delivery of material and teacher evaluation, and improve understanding of Arabic vocabulary and structure in a more contextually relevant way. These findings confirm that integrating traditional methods such as talaqqi and sorogan with interactive digital technologies can yield learning models that are adaptive, effective, and relevant to the development of Islamic education in the 21st century. This research provides a conceptual and practical contribution in the form of a prototype of a technology-based Arabic learning model that can be adapted in various Islamic educational institutions